Speech pathologists' current practice with cognitive-communication assessment during post-traumatic amnesia: A survey. (July 2013) - Steel, Joanne; Ferguson, Alison; Spencer, Elizabeth; Togher, Leanne
Abstract Primary objective: To investigate speech pathologists' current practice with adults who are in post-traumatic amnesia (PTA). Method: Speech pathologists with experience of adults in PTA were invited to take part in an online survey through Australian professional email/internet-based interest groups. Results: Forty-five speech pathologists responded to the online survey. The majority of respondents (78%) reported using informal, observational assessment methods commencing at initial contact with people in PTA or when patients' level of alertness allowed and initiating formal assessment on emergence from PTA. Seven respondents (19%) reported undertaking no assessment during PTA. Clinicians described using a range of techniques to monitor cognitive-communication during PTA, including static, dynamic, functional and impairment-based methods. Conclusions: The study confirmed that speech pathologists have a key role in the multidisciplinary team caring for the person in PTA, especially with family education and facilitating interactions with the rehabilitation team and family. Decision-making around timing and means of assessment of cognitive-communication during PTA appeared primarily reliant on speech pathologists' professional experience and the culture of their workplace. The findings support the need for further research into the nature of cognitive-communication disorder and resolution over this period.